Let a 1 , a 2 , … , a n be the roots of the polynomial k = 1 ∑ n k x k = 0 . If k = 1 ∑ n ( 1 − a k ) 2 1 = − 1 3 , find n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
thank you for your solution,sir (+1) ↑ . This is fantastic, in all ellegant senses of this word.
I did this by a similar method, except for me it felt more like a combinatorics problem because I converted the sums without the useful substitution. I would post my solution but 1. It's too similar and 2. it would be too hard to Latex it. Great problem & solution!!
Let f ( x ) = 1 ∑ n i x i = n 1 ∏ n ( x − x i )
We know, 0 ∑ n x i = x − 1 x n + 1 − 1 d x d 0 ∑ n x i = 0 ∑ n i x i − 1
So, f becomes, f ( x ) = x d x d x − 1 x n + 1 − 1 = ( x − 1 ) 2 x ( n x n + 1 − ( n + 1 ) x n + 1 )
We know 1 is not a root. So, we can use limit value to get f ( 1 ) or use sum of A.P formula. f ( 1 ) = x → 1 lim ( x − 1 ) 2 x ( n x n + 1 − ( n + 1 ) x n + 1 ) = 0 ∑ n i = 2 n ( n + 1 )
f ′ ( 1 ) = 0 ∑ n i 2 = 6 n ( n + 1 ) ( 2 n + 1 )
f ′ ′ ( 1 ) = x → 1 lim d x d ( d x d [ ( x − 1 ) 2 x ( n x n + 1 − ( n + 1 ) x n + 1 ) ] ) = 2 4 ( n − 1 ) n ( n + 1 ) ( 3 n + 2 ) OR f ′ ′ ( 1 ) = 1 ∑ n k ( 2 k ) = 2 4 ( n − 1 ) n ( n + 1 ) ( 3 n + 2 )
Using formula, 1 ∑ n ( 1 − x i ) 2 1 = ( f ( 1 ) ) 2 ( f ′ ( 1 ) ) 2 − f ′ ′ ( 1 ) f ( 1 ) , we get − 1 3 = 1 8 − n 2 + 1 1 n + 8
So, n = − 1 1 , 2 2
Taking positive value, n = 2 2
Proof for the above formula,
Suppose f ( x ) = k 1 ∏ n ( x − x i )
Differentiating once, f ′ ( x ) = 1 ∑ n x − x i f ( x ) = f ( x ) 1 ∑ n x − x i 1
So, 1 ∑ n x − x i 1 = f ( x ) f ′ ( x )
Differentiating again, f ′ ′ ( x ) = 1 ∑ n [ x − x i f ′ ( x ) − ( x − x i ) 2 f ( x ) ] = f ′ ( x ) ⋅ f ( x ) f ′ ( x ) − f ( x ) 1 ∑ n ( x − x i ) 2 1 ⇒ 1 ∑ n ( x − x i ) 2 1 = ( f ( x ) ) 2 ( f ′ ( x ) ) 2 − f ′ ′ ( x ) f ( x )
I came up with a technique to solve this problem, but after trying higher and higher degree polynomials, I eventually gave up and used Matlab. So I figured I better redeem myself by posting a real solution based on the technique I came up with. I will use my own method to derive a polynomial in n and find the roots, as in the other solutions. I divided by x to get rid of the zero root (call it a 1 ). Therefore, I was looking for when ∑ k = 2 n ( 1 − a k ) 2 1 = − 1 4 . I started by creating two polynomials of degree n − 1 , one with roots 1 − a k ( 2 ≤ k ≤ n ), and the other with roots a k − 1 ( 2 ≤ k ≤ n ). Respectively, these polynomials take the form P 1 ( x ) = ∑ k = 1 n k ( 1 − x ) k − 1 and P 2 ( x ) = ∑ k = 1 n k ( 1 + x ) k − 1 . I can factorize them in the following way: P 1 ( x ) = ( k = 1 ∑ n k ) ( 1 − 1 − a 2 x ) ( 1 − 1 − a 3 x ) . . . ( 1 − 1 − a n x ) and P 2 ( x ) = ( k = 1 ∑ n k ) ( 1 + 1 − a 2 x ) ( 1 + 1 − a 3 x ) . . . ( 1 + 1 − a n x ) The product of these two polynomials can be written as P 1 ( x ) P 2 ( x ) = ( k = 1 ∑ n k ) 2 ( 1 − ( 1 − a 2 ) 2 x 2 ) ( 1 − ( 1 − a 3 ) 2 x 2 ) . . . ( 1 − ( 1 − a n ) 2 x 2 ) The x 2 coefficient is given by ( ∑ k = 1 n k ) 2 ( − ∑ k = 2 n ( 1 − a k ) 2 1 ) = 1 4 ( ∑ k = 1 n k ) 2 . Now consider each polynomial in standard form (using the binomial theorem) and take their product: P 1 ( x ) P 2 ( x ) = ( k = 1 ∑ n k − x k = 1 ∑ n k ( k − 1 ) + x 2 k = 1 ∑ n 2 k ( k − 1 ) ( k − 2 ) + O ( x 3 ) ) ( k = 1 ∑ n k + x k = 1 ∑ n k ( k − 1 ) + x 2 k = 1 ∑ n 2 k ( k − 1 ) ( k − 2 ) + O ( x 3 ) ) From this I find another expression that represents the x 2 coefficient. Equating the two: ( k = 1 ∑ n k ( k − 1 ) ( k − 2 ) ) ( k = 1 ∑ n k ) − ( k = 1 ∑ n k ( k − 1 ) ) 2 = 1 4 ( k = 1 ∑ n k ) 2 2 n ( n + 1 ) ( 4 n 2 ( n + 1 ) 2 − 2 n ( n + 1 ) ( 2 n + 1 ) + n ( n + 1 ) ) − ( 6 n ( n + 1 ) ( 2 n + 1 ) − 2 n ( n + 1 ) ) 2 = 1 4 4 n 2 ( n + 1 ) 2 Next, divide by 4 n 2 ( n + 1 ) 2 to obtain 2 n ( n + 1 ) − ( 2 n + 1 ) + 2 − ( 3 2 n + 1 − 1 ) 2 = 1 4 This reduces to n 2 − 1 1 n − 2 4 2 = 0 which, has roots n = − 1 1 , 2 2 . Wait. -11??!... lol
Problem Loading...
Note Loading...
Set Loading...
If f ( X ) = ∑ k = 1 n k X k has roots a j for 1 ≤ j ≤ n , then putting X = 1 − Y − 1 = Y Y − 1 yields g ( Y ) = k = 1 ∑ n k ( Y − 1 ) k Y n − k as the polynomial with roots ( 1 − a j ) − 1 for 1 ≤ j ≤ n . Now g ( Y ) = = Y n k = 1 ∑ n k − Y n − 1 k = 1 ∑ n k 2 + Y n − 2 k = 1 ∑ n k ( 2 k ) + . . . 2 1 n ( n + 1 ) Y n − 6 1 n ( n + 1 ) ( 2 n + 1 ) Y n − 1 + 2 4 1 n ( n + 1 ) ( n − 1 ) ( 3 n + 2 ) Y n − 2 + . . . so j ∑ 1 − a j 1 = 3 1 ( 2 n + 1 ) j < k ∑ ( 1 − a j ) ( 1 − a k ) 1 = 1 2 1 ( n − 1 ) ( 3 n + 2 ) and so j ∑ ( 1 − a j ) 2 1 = 9 1 ( 2 n + 1 ) 2 − 6 1 ( n − 1 ) ( 3 n + 2 ) = 1 8 1 ( 8 + 1 1 n − n 2 ) We need to solve 1 8 1 ( 8 + 1 1 n − n 2 ) = − 1 3 , which factorises as ( n − 2 2 ) ( n + 1 1 ) = 0 , and so n = 2 2 .